Terraced vineyards - architectural responses - Simon, Marianna; Harea, Olga (4D Journal of Landscape Architecture and Garden Art, 2025)
The very first vine-growing landscapes were modelled in the primary era, some 260 million years ago. The vineyards became established preferentially on embankments, the edges of faults, and pebbly plains, as well as volcanic soil, millions of years later. A unique characteristic of the viticultural landscape are the terraced vineyards sustained by dry walling, a perfect example of landscape architecture created by man in inaccessible surroundings. Viticultural use was particularly predominant in the historic terraced landscape found across Europe: in the Cinque Terre region of Italy, by Banyuls-sur-Mer on the Mediterranean coast and Condrieu in the Rhône Valley in France, along the Douro in Portugal, on the Pelješac peninsula in Croatia, in Austrian Wachau, in the Swiss cantons of Ticino, Vaud and Valais, and in the valleys of the Ahr, Elbe, Mosel, Neckar, Rhine, and in their side valleys in Germany. They are the real evidence of how human life can express itself in the steepest slopes of mountain and coastal areas.